2022
DOI: 10.55730/1300-0527.3424
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of electrospun cellulose-derived nanofiber membranes with enhanced stability properties of arginase

Abstract: In this study, cellulose acetate (CA)/polyvinylpyrrolidone (PVP) and CA/PVP/Mn 2+ nanofibers were produced by the electrospinning method, and these cellulose-derived membranes were used as carriers for arginase immobilization for the first time. The structural and morphological analysis of these cellulose-derived nanofibers were determined by attenuated total reflection-Fourier to transform infrared spectroscopy (FTIR), thermogravimetric analysis (TGA), X-ray diffraction (XRD), and scann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 42 publications
0
0
0
Order By: Relevance
“…In the second stage, which is the main degradation step, it was observed that 88% of the mass was removed from the structure between 390 and 480 °C. It was stated in previous studies that the mass loss occurring in this step was due to the main thermal degradation reactions of CA chains. , In the last step, observed between 480 and 700 °C, approximately 93% of the initial mass was observed to move away from the structure. Additionally, it was determined that the maximum decomposition temperature of CA was 450 °C from the DTG curve.…”
Section: Resultsmentioning
confidence: 99%
“…In the second stage, which is the main degradation step, it was observed that 88% of the mass was removed from the structure between 390 and 480 °C. It was stated in previous studies that the mass loss occurring in this step was due to the main thermal degradation reactions of CA chains. , In the last step, observed between 480 and 700 °C, approximately 93% of the initial mass was observed to move away from the structure. Additionally, it was determined that the maximum decomposition temperature of CA was 450 °C from the DTG curve.…”
Section: Resultsmentioning
confidence: 99%